The Educational Situation and Digital Technologies According to The International Commission on The Futures of Education of Unesco - Hugo GONZÁLEZ (Communications of International Proceedings, 2023)
This study analyzes the educational situation and digital technologies from the perspective of the UNESCO International Commission that was created in 2019. A content analysis has been carried out with the Atlas ti program, taking into account the problems, proposals or actions educational and technological within the context of COVID-19. It is concluded that educational problems are related to others (such as political and economic). Also, within the technological problems are the lack of internet access, the increase in digital gaps that prevent quality education. For this, Unesco proposes an education that promotes the practice of democracy, the promotion of government policies that put into practice the technologies for transformation and innovation of education through access to the Internet and digital platforms.
Keywords: Educational situation; digital technologies; digital gaps; poverty; educational exclusion; virtual platforms